National Fisheries Sector of The Republic of Moldova: An Economic Overview - Mihaela MUNTEANU PILA; Silvius STANCIU (Communications of International Proceedings, 2022)
The paper proposes the presentation of specific aspects of the fisheries sector in the Republic of Moldova, related to the development, growth and capitalization of the production of fishery products in aquaculture, given the need for competitive integration on the world market. The study was based on the collection of statistical data provided by the National Bureau of Statistics of the Republic of Moldova, the World Food and Agriculture Organization (FAO), the World Trade Organization, the European Commission of the EU. The Clarivate Analytics, ResearchGate and Google Scholar databases were used for documentation. The analysis showed a low production of fish and processed fish products, respectively an average annual consumption per capita below the European average. Although the Republic of Moldova has a tradition in aquaculture, there is little use of the available natural resources. The development of demand, against the background of the positive evolution of the population's consumption, in the conditions of a modest increase of the domestic production, makes the domestic market more and more dependent on imports. The absence of national strategies to grow the fisheries sector, the insufficient funds allocated to producers, the lack of measures to encourage production and processing at national level will increase dependence on imports and reduce national food security indices.
Keywords: fish production. consumption; circular economy; sustainability; Republic of Moldova